EXPLORING THE INFLUENCE OF ORGANIZATIONAL CULTURE AND TRAINING ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AS HUMAN CAPITAL: REVIEW OF THE INTERNATIONAL SCIENTIFIC JOURNAL - Syaefunnur Maszah; Martinus Tukiran; Wahyu Wiguna; Ika Pratiwi; Ujo Sujoto (International Journal of Economy, Education and Entrepreneurship, 2023)
The extra-role behavior required for superior performance is also known as organizational citizenship behavior (OCB). Previous research findings highlight the positive contribution of OCB to superior organizational performance, as OCB encourages employees to participate spontaneously and dedicate themselves to organizational issues, both of which increase organizational efficiency and performance without additional expenditure. The purpose of this research is to examine the structural influence between training and organizational culture, with organizational citizenship behavior (OCB) as Human Capital, so in particular, this study emphasizes the effect of influence on the relationship between training and organizational culture on OCB as Human Capital. The accuracy of the measures involved were checked through conducting a factor review of the scientific literature or a review of three international journal articles by relational analysis. This review begins with identifying the main topics in Organizational Citizenship Behavior (OCB). The database used is Google Scholar and Harzing's Publish or Perish is limited to publication from 2017-2023. The review uses 3 articles that meet the theme criteria. This review found that training and organizational culture have a positive relationship on OCB as Human Capital which has a positive effect on improving employee and organizational performance. The implication is that corporation must invest in human resources as Human Capital, with the consequence of allocating finances and time, through training and building organizational culture, bearing in mind that the concept of human capital has brought major changes to human resource management that have a positive impact on companies or organizations